The Effect of Pore Length on The Mechanical Properties of Vascular Scaffold Due to Systolic Pressure (Journal of Medical Device Technology, 2023)
Tissue replacements are highly limited due to the lack of vascularized tissue in the engineered tissue. Thus, incorporating the vascular scaffold in any injured tissue or organ is critical in the tissue regeneration. As one of elastic tissue in human body, mechanical properties are vital in engineering a vascular scaffold. Besides, interconnected pores and scaffold porosity are among the main considerations in designing the scaffold for allowing the vascularization. Therefore, this study aims to simulate the mechanical properties of three-dimensional (3D) printed vascular scaffold by observing the deformation and elasticity after being applied with the maximum systolic pressure. Scaffolds with three different pore lengths were simulated for compression and tensile analysis by using Finite Element Analysis (FEA) based on polyethylene terephthalate (PET) material’s properties. The findings indicated that effective elastic modulus of the vascular scaffolds varied based on the pore length with shortest pore length gave the highest elasticity, whilst scaffold with the longest pore length gave lowest elasticity. Besides, stress value of compression and tensile analysis for all scaffolds were did not exceed the PET’s yield strength that indicated the designed scaffolds will have high potential for vascular tissue engineering applications.
Keywords: 3D-Printing; Vascular scaffold; Systolic pressure; Compression; Tensile